Пошаговое объяснение:
1) 3x - 15 - x - 3 = 0
2x - 18 = 0
2x = 18
x = 9
2) 7 - 3x - x - 11 = 0
-4x = 4
x = -1
3) 2x + 6 - x - 13 = 0
x - 7 = 0
x = 7
4) 20 - 4x - 3x + 1 = 0
7x = 21
x = 3
5) 3х - 6 - х - 4 = 0
2х - 10 = 0
2х = 10
х = 10/2
х = 5
6) 5x - 5 - 4x - 3 = 0
x - 8 = 0
х = 8
Пошаговое объяснение:
1) 3x - 15 - x - 3 = 0
2x - 18 = 0
2x = 18
x = 9
2) 7 - 3x - x - 11 = 0
-4x = 4
x = -1
3) 2x + 6 - x - 13 = 0
x - 7 = 0
x = 7
4) 20 - 4x - 3x + 1 = 0
7x = 21
x = 3
5) 3х - 6 - х - 4 = 0
2х - 10 = 0
2х = 10
х = 10/2
х = 5
6) 5x - 5 - 4x - 3 = 0
x - 8 = 0
х = 8
Пошаговое объяснение: